Discourse on Character Education of the Main Character Enong in the Novel Padang Bulan by Andrea Hirata - Sofhan, Irfan Kholid; Suaedi, Hasan; Afrizal, Mohamad (Journal of Language and Literature Studies, 2025)
This study aims to analyze the character education discourse reflected through the main character, Enong, in the novel Padang Bulan by Andrea Hirata using F.W. Foerster's character education theory. The methodological approach employed is discourse analysis with descriptive qualitative methods. The research data consist of narrative excerpts and dialogues reflecting the character values of Enong, which are then classified based on Foerster's four main principles: orderliness (discipline), adherence to values (obedience to values), loyalty, and integrity of life (unity of life). The research findings indicate that the character education discourse in this novel is manifested through two main aspects: learning motivation and hard work. Learning motivation is reflected in Enong's enthusiasm for continuously pursuing knowledge, diligence in self-directed learning, and loyalty to her aspirations despite living in economic and social limitations. Meanwhile, the value of hard work is evident in Enong's persistence in bearing the family's economic burden, courage in taking on the role of a tin prospector, and resilience in facing failure without giving up. All four of Foerster's principles are consistently present in Enong's actions and words, demonstrating the integration of moral, intellectual, and social values. This study concludes that Andrea Hirata successfully constructs a humanistic character education discourse through the figure of Enong as a representation of a resilient, independent, and educated woman. These findings are relevant for use as literary teaching materials in character education learning in schools because they contain universal values such as discipline, responsibility, determination, and loyalty to one's aspirations.